The Effectiveness of Using Wordwall to Improve Vocabulary Mastery of The First Graders at MTs Futuhiyyah Bumirejo - Faqiah, Wulida Nurul; Ungu, Niken Kencono (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
The objectives of this study are:1) To know how to improve vocabulary mastery in the first graders at MTs Futuhiyyah Bumirejo. 2) To create interesting vocabulary learning media that suits the needs of students in the first graders at MTs Futuhiyyah Bumirejo. 3) To use of wordwall media in the first graders at MTs Futuhiyyah Bumirejo in helping to improve learning activities. The research method used is a true experimental research method. The basic approach to the experiment involves the activities of researchers starting from observations about the level of vocabulary maintenance possessed by first grade students of MTs Futuhiyyah Bumirejo. Based on the research include the following 3 things: 1) For the first hypothesis, how the use of wordwall affects the level of vocabulary mastery of students. This is evidenced by the value of Tcalculate 4,000 greater than Ttable 2,005. 2) The second hypothesis, that there is an increase in scores from the experimental class pretest and experimental class postest obtained after the treatment using wordwall media. 3) The third hypothesis how to result in the Pretest Postest-Control Class value with the Pretest Postest-Experiment Class. This can be seen from the results of the scores of each test. Based on the result, it was able to know were the difference of the students score in post-test of control and experimental class in vocabulary mastery. Result of experimental class found the highest score was 90,00, the lowest score was 70,00. In post-test of the control class found the highest score was 85,00, and the lowest was 55,00. So it can be concluded from the second hypothesis that there is a significant ability by the Experimental class with the experimental using wordwall media to improve students' vocabulary mastery.